The Role of HPV in Oropharyngeal Cancer: Diagnosis, Treatment, and Prognosis - Erkinovich, Shodiyev Anvar; Saydullo o'g'li , Bo'riyev Shaxzod (Journal of Science in Medicine and Life, 2025)
Human papillomavirus (HPV) has emerged as a major etiological factor in a subset of oropharyngeal squamous cell carcinomas (OPSCC), particularly affecting younger, non-smoking individuals. This article explores the virology of HPV, its oncogenic mechanisms, and its distinct epidemiological and clinical features in oropharyngeal cancer. We provide an extensive review of diagnostic approaches, current treatment paradigms including surgery, radiotherapy, and immunotherapy, and explore the evolving landscape of prognosis and surveillance. This multidisciplinary synthesis aims to inform ENT specialists, oncologists, and researchers on the changing profile of oropharyngeal cancer in the HPV era.